All Hands on Deck : Reducing Stunting through Multisectoral Efforts in Sub-Saharan Africa - World Bank Group (World Bank, Washington, DC, 2018)
As part of the effort to understand the underlying multisectoral nature of improving nutrition outcomes in sub-Saharan Africa, stylized country specific analyses were carried out for the 33 countries in the study. The methodology used for the regional study was applied at the country level, and the results are offered as a starting point for understanding and evaluating the multisectoral dimensions of nutrition in specific country contexts. The briefs layout the prevalence of stunting and access to nutrition determinants in the country, for select subpopulations within the country, and regionally. Briefs provide a useful starting point for diving deeper into the interplay of multisectoral determinants and nutrition in a country, they are just that, a starting point.